THE EFFECT OF INDUSTRIAL WORK PRACTICES, LEARNING ACHIEVEMENT, AND WORK MOTIVATION ON STUDENT WORK READINESS OF SMKN 14 JAKARTA - Nadya Fadillah Fidhyallah; Nurjana Fitri Romadhon; Corry Yohana (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
The purpose of this study was to determine the effects of industrial work practices (X1), learning achievement (X2), and work motivation (X3) on students' work readiness (Y). The research method used is quantitative. The population of this research is the XII grade students of SMKN 14 Jakarta and the sample is 161 students with a Likert. The sampling technique used is proportional random sampling. The data analysis technique used was SPSS version 25. The results of hypothesis testing indicated by multiple linear regression analysis consisted of T test and F test. The results showed that there was an influence between industrial work practices and work readiness; there was no influence between learning achievement and work readiness; there was an influence between work motivation and work readiness; and industrial work practices, learning achievement, and work motivation have a simultaneous influence on job readiness.